Anscombe’s Moral Epistemology and the Relevance of Wittgenstein’s Anti-Scepticism - Michael Wee (Enrahonar: Quaderns de Filosofia, 2020)
Elizabeth Anscombe is well-known for her insistence that there are absolutely prohibited actions, though she is somewhat obscure about why this is so. Nonetheless, I contend in this paper that Anscombe is more concerned with the epistemology of absolute prohibitions, and that her thought on connatural moral knowledge – which resembles moral intuition – is key to understanding her thought on moral prohibitions. I shall identify key features of Anscombe’s moral epistemology before turning to investigate its sources, examining the roots of connaturality in Aquinas and comparing it with rationalist ethical intuitionism, which Anscombe differs from in rejecting “good” as a simple, non-natural property. I then develop a two-stage argument about absolute prohibition: The first will be loosely Thomistic, while the second will suggest how Anscombe’s absolute prohibitions can be seen as a continuation of Wittgenstein’s anti-scepticism in On Certainty. I develop an account of absolute prohibitions as a form of Wittgensteinian hinge proposition – they are not the conclusions of deductive arguments, but the foundations for intelligibility in action.